KECERDASAN GENDER DALAM KEPEMIMPINAN POLITIK PERSPEKTIF AL-QURAN - Nur Arfiyah Febriani; Daiyyana Sari (LP2M Universitas PTIQ Jakarta, 2025)
The conclusion of this article is that the formulation of the concept of gender intelligence in political leadership contains ideas and inspirations to be implemented in managing political power. The formulation of gender intelligence consists of four aspects: First, The ability of leaders to understand the equality of political rights of men and women in the scope of political power. Second, The ability of leaders to apply male and female thinking tendencies in managing political power.Third, The ability of leaders to apply male and female thinking tendencies in managing political power. Fourth, The ability of leaders to apply models of emotional regulation in managing political power. The representation of a gender-intelligent leader is characterized by the ability to balance femininity and masculinity, bringing the worldly dimension to the spiritual dimension (Divinity). So that leaders are able to arouse, influence and move through exemplary behavior, service, compassion, to achieve political goals.